Why do xenarthrans matter? - Superina, Mariella (2015)
Xenarthrans possess a suite of characteristics that make them among the most unusual of mammals. Understanding the functional significance of these traits is one prominent reason why xenarthrans matter. In addition, Xenarthra is currently considered one of the basal clades of placental mammals, and the only one to originate in South America. Consequently, studies of xenarthrans can provide important insights into the evolution of early placentals. The fossil record contains hundreds of recognized species of xenarthrans but this rich evolutionary history is currently distilled into just 31 extant species. Preserving this heritage through various conservation initiatives is yet another reason why xenarthrans matter. This Special Feature on xenarthrans provides an overview of current work and identifies many areas requiring further study. It is our hope that this Special Feature will raise the profile of xenarthrans among mammalogists and perhaps entice some to consider addressing one or more of the many lingering questions that remain about this enigmatic group.